Vibrational branching ratios and hyperfine structure of 11BH and its suitability for laser cooling - Hendricks, R. J.; Holland, D. A.; Truppe, S.; Sauer, B. E.; Tarbutt, M. R. (Frontiers in Physics, 2014)
The simple structure of the BH molecule makes it an excellent candidate for direct laser cooling. We measure the branching ratios for the decay of the A1Π (v′ = 0) state to vibrational levels of the ground state, X1Σ+, and find that they are exceedingly favorable for laser cooling. We verify that the branching ratio for the spin-forbidden transition to the intermediate a3Π state is inconsequentially small. We measure the frequency of the lowest rotational transition of the X state, and the hyperfine structure in the relevant levels of both the X and A states, and determine the nuclear electric quadrupole and magnetic dipole coupling constants. Our results show that, with a relatively simple laser cooling scheme, a Zeeman slower and magneto-optical trap can be used to cool, slow and trap BH molecules.